The Relationship between Knowledge, Attitude, and Performance in Breast Cancer with Nutritional Behaviors and Drug Use - Falah Asadi, Ayda; Shahsavari, Saeed; Khosravizadeh, Omid; Nourmohammadi, Mohammad (Asian Pacific Journal of Environment and Cancer, 2018)
Breast cancer is the most common cancer in women, and tobacco and alcohol usage as well as inappropriate diet are some risk factors for developing this cancer. On the other hand, breast self-examination is a simple, effective, and cheap method for screening and early detection of breast cancer that is accessible for most of women. The aim of this study was to assess the correlation between knowledge, attitude, and performance in the case of breast cancer, with nutritional behaviors and tobacco use. In this descriptive-analytical study, studied population was all women over 15 years old, who were referred to health and treatment center of Buin-Zahra in 2018. The sample size was 250 cases according to a pilot study. Sampling method was random simple sampling, and data were collected using interview method. Data collection tool included two questionnaires (questionnaire of knowledge, attitude, and performance in the case of breast cancer, and questionnaire of life style in the case of tobacco use and diet). Collected data entered SPSS 25 software and Pearson’s correlation test, T-test, and ANOVA were used for data analysis. Most of the studied cases were in 26-30 years old age group (32.8%). 54.8% had diploma, 88% were married, and 90.8% were house-wives. It was indicated that 7% of cases had monthly self-examination and 82.8% had no mammography experience. There was a positive correlation between knowledge and performance about breast cancer, and nutritional status. There were also a significant correlation between age and performance (p-value: 0.044), education level and knowledge (p-value: 0.003), and attitude (p-value: 0.029), marriage status and performance (p-value: 0.002), and occupational type and performance (p-value: 0.001). It is shown that there is a significant correlation between education level, knowledge and attitude. So, it is recommended that educational effective programs should be used in the health and treatment centers to increase the level of knowledge and attitude of women about breast cancer, and to alter life style pattern in the case of tobacco use (as an environmental factor), and to alter nutritional pattern.